Relational Climate in the Workplace: Dimensions, Measurement, and Validation - Boyatzis, Richard E.; Rochford, Kylie (Frontiers in Psychology, 2020)
Relationships are the fundamental building block of organizations, yet the field lacks a validated and comprehensive measure of how employees perceive the quality of the relationships in their organization. In this paper, we develop and validate a scale to measure the perceived relational climate in an organization. We operationalize relational climate as a second-order latent construct reflected by three first-order constructs: shared vision, compassion, and relational energy. In Study 1, we develop an item pool consisting of 51 items and then use a Q-sort procedure to assess content validity. In Study 2 the item pool is further reduced using exploratory factor analysis. This is followed by a confirmatory factor analysis that finds initial support for the three-dimension structure of relational climate. Study 3 provides further evidence of convergent and discriminant validity and assesses the criterion validity of the construct in relation to LMSX, perceived organizational support, and procedural justice (all positive relationships). Finally, in Study 4, the factor structure of quality of relationships scale is successfully replicated and criterion validity is further assessed in relation to instrumental ethical climate (negative relationship) and affective organizational commitment (positive relationship). This paper contributes a new validated measure to the literature that will allow organizations to capture an important aspect of their work environment – the nature of the interpersonal relationships. Implications for theory, limitations, and future research are discussed.